The Effects of Policy Uncertainty on Stock Prices: Revisiting with Selected Countries - Durmaz, Nazif (Ekonomika, 2024)
Released by Policy Uncertainty, the economic policy uncertainty (EPU) index is built on newspaper reports that contribute to uncertain conditions. The present study examines the impact of the EPU index on stock price indices on a selected group of countries. Variations in stock price indices are explained in a similar fashion as in previous studies but this study employs a new dataset. To obtain the speeds of adjustment to long-run equilibrium and short-run elasticities in every country, the framework of error correction was applied. This paper concludes that increased uncertainty has unfavorable short-run effects in all countries in the dataset. The present study also reports negative relation in the long run between high uncertainty and stock prices in some countries.
Keywords: Policy uncertainty; stock prices; ARDL